Exploration of mining heritage and evaluation of mining tourism potential in the La Ferrería village, mining territory of the municipality of Amagá, in the northwestern Colombian Andes - Luis Hernán Sánchez-Arredondo; Andrés López-Gómez; Sergio Alejandro Garavito-Higuera (International Journal of Geoheritage and Parks)
The influence of mining activity in the northwestern Andes of Colombia is evident in the creation and development of various settlements, such as La Ferrería village in the municipality of Amagá, in the formation of the working-class culture, and in the shaping of the region's natural and social structures. This study explored the potential for mining tourism in La Ferrería, as a strategy to diversify the local economy and preserve mining heritage. Through surveys of local communities, interviews, and the analysis of historical documents, information was gathered regarding community perceptions, the condition of mining heritage, and opportunities for mining tourism development as a specialized form of geotourism for the region. The results indicated significant potential for mining tourism development, but challenges related to heritage conservation, infrastructure, and training were also identified. It is concluded that mining tourism can be an effective tool for the economic and social revitalization of the southwestern Antioquia region, specifically La Ferrería village, provided that an integrated management plan is implemented, which involves the local community and addresses environmental and social challenges.